Providing TikTok platform to educate public regarding customs - Septiana Dwiputrianti; Difta Arcellya Putri Atmadiharja; Soufhi Lautza; F Laksmi Fitriani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Lack of understanding of regulations related to customs and excise services has resulted in rampant fraud on behalf of the Customs and Excise office and the blocking of imported mobile phones due to unregistered or illegal International Mobile Equipment Identity (IMEI). Community service activities (PKM) aim to educate the public about various rules and IMEI registration of electronic devices as imported goods, including the terms and conditions that the public must meet through the creation and use of the TikTok platform. The method used is AIDA so that the media and content produced are clear, concise, creative, and interesting so that it is easy for the public to understand. The TikTok platform was created and developed as an effective medium for educating the public through disseminating information that can increase awareness and knowledge of the wider community. This approach illustrates the various common fraud modes and how to identify them. There is also content about the Bandung Customs Office call center and office-tour services for official transparency and professionalism in handling various public complaints. The number of followers who support this and like that has increased significantly from time to time. Information using the TikTok platform related to official customs and excise service issues has significantly reduced the number of frauds by irresponsible individuals, and cases of IMEI blocking.